TRAINING ON PROPOSAL MAKING OF TRADITIONAL RANGE FESTIVAL SPONSORS IN DUKUH DEMPING, ANGGRASMANIS, JENAWI, KARANGANYAR - Hapsari, Dian Indriana; Hariyadi, Guruh Taufan; Ratnawati, Juli; Pamungkas, Imang Dapit (International Journal of Social Science, 2022)
Advances in science, technology and science are developing so rapidly. But unfortunately technological progress is not followed by moral, ethical and spiritual progress. Based on the information presented, it can be concluded that the basic problem in the "Community of Tinthir Nusantara" group is the lack of knowledge and understanding of the participants and managers of the traditional snacks festival in making an attractive proposal that will be submitted to the sponsor. Therefore, a program namely the introduction and training of the importance of recognizing Virtual Reality in everyday life as well as in marketing strategies to improve the welfare of the surrounding Community is needed. The training can be used to manage the implementing management as well as promote the activity in order to attract sponsors, so people from other region will interest to join the festival. With this technology, management is expected to be able to improve managerial skills and carry out promotions outside the region. In addition, this training serves as a means of information for the Demping Tourism Village and serves as material for evaluating activities by the manager of the Demping Tourism Village for the next implementation.